Seismogenic structures in Quaternary lacustrine deposits of Lake Van (eastern Turkey) - Üner, Serkan (Geologos, 2014)
Soft-sediment deformation structures formed by liquefaction and/or fluidisation of unconsolidated sediments due to seismic shocks are frequent in the Quaternary sandy, silty and clayey deposits of Lake Van. They are present in both marginal and deep lacustrine facies. Their morphology and interpreted genesis imply that they should be considered as fluid-escape structures (dish and pillar structures, flame structures and sand volcanoes), contorted structures (simple and complex convolutions and ball-and-pillow structures) and other structures (disturbed layers and slump structures). The most recently formed structures are related to the October 23rd, 2011 Van-Tabanli (M 7.2) earthquake. The existence of seismites at various stratigraphic levels in the lacustrine deposits is indicative of tectonic activity that frequently triggered earthquakes with magnitudes of 5 or more, affecting the Lake Van Basin.